2014
DOI: 10.1016/j.ygeno.2014.01.001
|View full text |Cite
|
Sign up to set email alerts
|

One in four individuals of African-American ancestry harbors a 5.5 kb deletion at chromosome 11q13.1

Abstract: Cloning and sequencing of 5.5kb deletion at chromosome 11q13.1 from the HeLa cells, tumorigenic hybrids and two fibroblast cell lines has revealed homologous recombination between AluSx and AluY resulting in the deletion of intervening sequences. Long-range PCR of the 5.5kb sequence in 494 normal lymphocyte samples showed heterozygous deletion in 28.3% of African- American ancestry samples but only in 4.8% of Caucasian samples (p<0.0001). This observation is strengthened by the copy number variation (CNV) data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…We and others have shown that a cervical cancer tumor suppressor gene is localized to chromosome 11q13 and that genomic rearrangements at this site are common in cervical and other human cancers (13,14). We have further shown that homozygous deletion of 5.5kb is seen in HeLa cell derived tumorigenic cell lines and primary tumors indicating the importance of these sequences in tumor development (15)(16)(17). Extensive mapping of the 300kb region localized the 5.5 kb sequence to the 1 st intron of PACS-1, a protein involved in cytoplasmic protein trafficking (15)(16)(17).…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…We and others have shown that a cervical cancer tumor suppressor gene is localized to chromosome 11q13 and that genomic rearrangements at this site are common in cervical and other human cancers (13,14). We have further shown that homozygous deletion of 5.5kb is seen in HeLa cell derived tumorigenic cell lines and primary tumors indicating the importance of these sequences in tumor development (15)(16)(17). Extensive mapping of the 300kb region localized the 5.5 kb sequence to the 1 st intron of PACS-1, a protein involved in cytoplasmic protein trafficking (15)(16)(17).…”
Section: Introductionsupporting
confidence: 52%
“…We have further shown that homozygous deletion of 5.5kb is seen in HeLa cell derived tumorigenic cell lines and primary tumors indicating the importance of these sequences in tumor development (15)(16)(17). Extensive mapping of the 300kb region localized the 5.5 kb sequence to the 1 st intron of PACS-1, a protein involved in cytoplasmic protein trafficking (15)(16)(17). The repetitive nature of the 5.5 kb sequence made it extremely difficult to functionally characterize the sequence for its role in tumor development.…”
Section: Introductionmentioning
confidence: 66%
“…The 11q13 locus is well known to contain fragile sites that are prone to breakage. This region has a high frequency of repeats, low GC content, two folate-sensitive fragile sites, potential secondary structures, and a high incidence of cytogenetic and molecular alterations in several cancers [ 55 , [58] , [59] , [60] , [61] ]. Structural variations (SV), which alter chromosomal structure and the DNA copy number, are increasingly recognized as major contributors to genome variability [62] .…”
Section: Fads and Elovl Biochemical Functionsmentioning
confidence: 99%
“…The genetic composition of human chromosome 11q13 is known to contain hotspots for viral integration, harbor fragile sites, copy number variations (CNV) (Figure 2), and various disease phenotypes, including several types of cancers (51)(52)(53)(54). The 11q13 locus is well known to contain fragile sites that are prone to breakage (55). This region has a high frequency of repeats, low GC content, two folate-sensitive fragile sites, potential secondary structures, and a high incidence of cytogenetic and molecular alterations in several cancers (51,(54)(55)(56)(57).…”
Section: Q13 Genomic Regionmentioning
confidence: 99%